Integrated 16S rRNA Gene Sequencing and Metabolomics Analysis to Investigate the Important Role of Osthole on Gut Microbiota and Serum Metabolites in Neuropathic Pain Mice - Li, Ruili; Wang, Fan; Dang, Shajie; Yao, Minna; Zhang, Wei; Wang, Jingwen (Frontiers in Physiology, 2022)
Accumulating evidence suggests that neuropathic pain is closely connected to the metabolic disorder of intestinal microbiota, and nature products could relieve neuropathic pain by regulating gut microbiota. The purpose of this study is to investigate the important regulatory effects of osthole on gut microbiome and serum metabolites in neuropathic pain mice. Mice’s intestinal contents and serum metabolites were collected from sham group, CCI group and osthole treatment CCI group. 16S rRNA gene sequencing analysis based on Illumina NovaSeq platform and ANOVA analysis were used to analysis the composition variety and screen differential express of intestinal bacteria in three groups. UHPLC-Q-TOF-MS was used for analyzing the data obtained from serum specimen and KEGG enrichment analysis was used to identity pathways of differential metabolites in the treatment of neuralgia mice. What's more, Pearson method and Cytoscape soft were used to analysis correlation network of differential metabolites, gut microbiota and disease genes. The analysis results of 16S rRNA gene sequencing displayed that Bacteroidetes, Firmicutes and Verrucomicrobia was highly correlated with neuropathic pain after osthole treatment at phylum level, and Akkermansia, Lachnospiraceae_unclassified, Lachnospiraceae_NK4A136_group, Bacteroroides, Lactobacillus and Clostridiales_unclassified genera are divided into higher relative abundance and important microbial members at genus level. Serum metabolomics results showed that 131 metabolites were considered to be significant difference in CCI group compared to sham group, and 44 metabolites were significantly expressed between osthole treatment group and CCI group. At the same time, we found that 29 differential metabolites in the two comparison groups were overlapping. Integrated analysis results showed that many intestinal microorganisms and metabolites have strong positive correlation. Correlation network diagram display that 10 genes were involved in the process of osthole alleviating neuropathic pain through metabolic pathway and gut microbiota, including IGF2, GDAP1, MYLK, IL18, CD55, MIR331, FHIT, F3, ERBB4, and ITGB3, et al. Our findings have preliminarily confirmed that neuropathic pain is closely related to metabolism and intestinal microbial imbalance, and osthole can improve the metabolic disorder of neuropathic pain by acting on intestinal microbiota.